CsrA-Mediated Translational Activation of ymdA Expression in Escherichia coli - Andrew Renda (American Society for Microbiology, 2020)
ABSTRACT The sequence-specific RNA-binding protein CsrA is the central component of the conserved global regulatory Csr system. In Escherichia coli, CsrA regulates many cellular processes, including biofilm formation, motility, carbon metabolism, iron homeostasis, and stress responses. Such regulation often involves translational repression by CsrA binding to an mRNA target, thereby inhibiting ribosome binding. While CsrA also extensively activates gene expression, no detailed mechanism for CsrA-mediated translational activation has been demonstrated. An integrated transcriptomic study identified ymdA as having the strongest CsrA-mediated activation across the E. coli transcriptome. Here, we determined that CsrA activates ymdA expression posttranscriptionally. Gel mobility shift, footprint, toeprint, and in vitro coupled transcription-translation assays identified two CsrA binding sites in the leader region of the ymdA transcript that are critical for translational activation. Reporter fusion assays confirmed that CsrA activates ymdA expression at the posttranscriptional level in vivo. Furthermore, loss of binding at either of the two CsrA binding sites abolished CsrA-dependent activation. mRNA half-life studies revealed that CsrA also contributes to stabilization of ymdA mRNA. RNA structure prediction revealed an RNA hairpin upstream of the ymdA start codon that sequesters the Shine-Dalgarno (SD) sequence, which would inhibit ribosome binding. This hairpin also contains one of the two critical CsrA binding sites, with the other site located just upstream. Our results demonstrate that bound CsrA destabilizes the SD-sequestering hairpin such that the ribosome can bind and initiate translation. Since YmdA represses biofilm formation, CsrA-mediated activation of ymdA expression may repress biofilm formation under certain conditions. IMPORTANCE The Csr system of E. coli controls gene expression and physiology on a global scale. CsrA protein, the central component of this system, represses translation initiation of numerous genes by binding to target transcripts, thereby competing with ribosome binding. Variations of this mechanism are so common that CsrA is sometimes called a translational repressor. Although CsrA-mediated activation mechanisms have been elucidated in which bound CsrA inhibits RNA degradation, no translation activation mechanism has been defined. Here, we demonstrate that CsrA binding to two sites in the 5′ untranslated leader of ymdA mRNA activates translation by destabilizing a structure that otherwise prevents ribosome binding. The extensive role of CsrA in activating gene expression suggests the common occurrence of similar activation mechanisms.